Design of North Sumatera Paradise Gallery in Medan City (Metaphor Architecture) - Robby Honoris; Andalucia . (International Journal of Architecture and Urbanism, 2017)
The purpose of this Art Gallery designing is for giving space for the local artist to place and promote their art products. It’s because Medan city has not decent gallery according to the national standard. The surplus of this art gallery out of showing fine art is giving room experience impression to support fine art showcase. The theme of the building is a metaphor of water ripple to represent Babura river, so the art installation to the building is using water concept that gives unique aspect to building and can be art identity of Medan city. This gallery building is hoped to fulfill gallery estimation which is decent in national and international rank because Medan is the third biggest town in Indonesia where been visited by so many foreign tourists.